HUBUNGAN KEBUTUHAN SPIRITUAL TERHADAP TINGKAT KUALITAS HIDUP LANSIA - Riyanti Vianica Sibuea; Mori Agustina br Perangin-angin (NUTRIX, 2020)
ABSTRACT Elderly is the final stage in human life. In this phase, you will experience physically,mentally, socially, and spiritually health problems that affected the quality of life of the elderly. Problems often faced by the elderly are loneliness and anxiety facing death. This problems requires spiritual support. Spiritual support can help the elderly reduce stress and anxiety. If spirituality is fulfilled, the quality of life will increase. This studywas to determine the relationship between spiritual support and the quality of life elderly. The design of this study was descriptive correlation method, with the respondent 30 elderly , aged 60 years or more and analyzed using Spearman-rho. The data collection technique used a questionnaire. SpNQ (Spiritual Needs Questionnaire) used to measued spiritual support and WHOQOL_BREF (WHO Quality of Life) to measured quality of life. The results showed a relationship between spiritual support and the quality of life of the elderly. With a significant value at the 0.01 level. Research suggestion that a community with many elderly people in it pay attention to their spiritual needs in order to improve the quality of life and live a more prosperous life. Keywords : Spiritual support, Quality of life, Elderly